Pengaruh Perputaran Piutang dan Periode Pengumpulan Piutang Terhadap Cash Inflow Pada PT Sucofindo (Persero) Cabang Bandar Lampung - Novi Maria; Muhammad Luthfi (Universitas Malahayati, 2014)
The purpose of this study is to find out whether the variables, turnover receivables andreceivables conversion periode , have influence to cash inflow. The sample that were used in thisresearch are the turnover receivables report, receivables conversion periode report, and cash inflowreport for 60 months of 2009-2013. Analyzing this research used multiple regression analysis withmeasurement of α 5%. The data analyzing in this research used a software of SPSS 17.0 (StatisticalPackage for The Social Science). Based on the calculation result on simultaneous test were obtainedFvalue was 20,868 and Pvalue (0,000). Pvalue (0,000)< α(0,05), in that case the turnover receivables andreceivables conversion periode have influence to cash inflow at PT SUCOFINDO (Persero) BandarLampung subdivision. Meanwhile, partially it has positive significant influence on the turnover ofreceivables to cash inflow with the tvalue was 3,519 and Pvalue 0,001< α (0,05). Then the receivablesconversion periode has negative significant influence to cash inflow at SUCOFINDO (Persero)Bandar Lampung subdivision with tvaluewas -2,115 and Pvalue 0,039. Pvalue 0,039 < α (0,05).